Acquired Dyslexia in Spanish: A Review and Some Observations on a New Case of Deep Dyslexia - Robert Davies; Fernando Cuetos (Behavioural Neurology)
Readers and writers of Spanish use an orthography that is highly transparent. It has been proposed that readers of Spanish can rely on grapheme-phoneme correspondences, alone, to access meaning or phonology from print. In recent years, a number of case studies have yielded evidence inconsistent with this idea. We review these studies with particular focus on those that report evidence for reading based on direct lexical mappings between print, orthographic representations, and meaning or phonology. We report a new case of acquired literacy impairment in Spanish, MJ, who presents a pattern of preserved abilities and deficits symptomatic of deep dyslexia. The patient is unable to read nonwords, but can read a substantial number of words. Her reading is characterized by the production of semantic, visual, and derivational errors. We argue that MJ has a deficit in her lexical selection ability, common to both her reading and her naming problems. We propose that MJ, and the other cases we review, demonstrate that lexical reading is adopted by skilled readers even in a transparent language.